A Rare Cause of Knee Pain in Gout Patients: Tophi of Patella - Ayhan AŞKIN; Rahime İNCİ and Özlem AKAN and Seçil DEMİRDAL and Korhan BAYRAM (Archives of Rheumatology, 2015)
Gout is a monosodium urate crystal deposit disease which generally occurs in middle-aged males and postmenopausal females. It is typically characterized by episodic acute and chronic arthritis, due to deposition of monosodium urate crystals in joints and connective tissue. Palpable deposits of crystals known as tophi may form particularly around joints but also elsewhere. Tophi can present as masses in many different body locations resulting in various clinical problems which are finally understood when the mass is sampled and analyzed. A 60-year-old male chronic tophaceous gout patient admitted to our hospital with complaints of bilateral patellar pain. After clinical, laboratory and radiological assessment, our diagnosis was consistent with patellar involvement of gouty tophi which is rarely seen. In this article, we present the clinical and radiological findings of a patient with bilateral severe patellar pain due to gouty tophi.